PERAN KEPEMILIKAN INSTITUSIONAL: PENGARUH RELATED PARTY TRANSACTION TERHADAP NILAI PERUSAHAAN - Fitri Nurjanah; Rosdiyati Rosdiyati; Indah Kurniyawati; Rizqi Rahman Putra Nurdiansyah (Jurnal Riset Akuntansi Politala, 2023)
The aim of this study is to prove the effect of related party transactions on firm value with the moderation of institutional ownership. The data analysis method used are descriptive statistics and hypothesis testing using the Moderated Regression on Analysis (MRA) methods and the Stata 14 application. The population in this study are all non-financial companies listed on the Indonesia Stock Exchange during 2017-2020. This study used a total sample of 363 companies. The results show that related-party transactions harm firm value that can raise concerns of minority shareholders that related-party transactions have the potential for tunelling that will harm them as minority shareholders. That causes capital market investors to react negatively to the company, thereby reducing the value of the company. Institutional ownership moderates the effect of related party transactions on firm value.